Challenges in Upholding Women’s Post-Divorce Rights: Experiences From Legal Practitioners in the Mataraman Region, East Java - Saputra, Wahyu; Ali Murtadlo, Muhammad; Haider, Aftab (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2024)
This article examines the fulfillment of womens' post-divorce rights initiated by the wife in the Religious Courts of the Mataraman Region, East Java. Applying the legal system and feminist legal theory, this article combines a normative juridical approach with case studies. The findings identify inconsistencies between the legal substance and its implementation in Mataraman Region, which affect the fulfillment of wives' rights after divorce. Law enforcement officers face challenges in enforcing these rules due to patriarchal culture and a lack of gender awareness. The legal culture within society also influences the process of fulfilling wives' rights, particularly concerning the impact of patriarchal culture and gender stereotypes. Utilizing feminist legal theory, gender bias in the application of the law often disadvantages women, indicating the urgent need for fundamental changes to achieve gender justice. Therefore, revising and harmonizing legal regulations in a more specific and detailed manner through implementing rules issued by the Supreme Court and enhancing gender awareness among law enforcement officers and the community is crucial to ensure the fair and equitable fulfillment of wives' rights post-divorce.